Diversity regimes : why talk is not enough to fix racial inequality at universities - Thomas, James M., 1982- (New Brunswick : Rutgers University Press, 2020)
"In Diversity Regimes, James M. Thomas uncovers a complex combination of meanings, practices, and actions that work to institutionalize universities' commitments to diversity, but in doing so obscure, entrench, and even magnify existing racial inequalities. Drawing on two years of ethnographic field work at so-called "Diversity University," Thomas provides new insights into the social organization of multicultural principles and practices"--Publisher's description
Introduction -- Under the live, old oak trees -- Condensation and the alchemy of diversity -- Go your own way: the organizational structure of diversity -- Staging difference, performing diversity -- Diversity regimes and the reproduction of racial in equality -- Appendix: studying inequality, in situ.
Includes bibliographical references and index.
Online resource; title from resource home page (JSTOR, viewed June 19, 2020).
JSTOR
Keywords: Discrimination in higher education -- United States; Educational equalization -- United States; Discrimination dans l'enseignement supérieur -- États-Unis.; Démocratisation de l'enseignement -- États-Unis.; EDUCATION -- General; Discrimination in higher education; Educational equalization; United States